Design of LMS Based Adaptive Beamformer for ULA Antennas - Truong, Giang Vu Bang; Tong, Luyen Van (VNU Journal of Science: Computer Science and Communication Engineering; Vol 32 No 3 (2016), 2016)
This paper proposes a design of an adaptive beamformer for arbitrarily uniformly spaced array (ULA) antennas. Least Mean Square (LMS), a prevalent adaptive beamforming algorithm, has been employed in the beamformer for the ULA antennas. A procedure has been introduced to validate the proposed design. Applying the proposal, a LMS based adaptive beamformer for 8Ã—1 ULA antennas has been built and implemented on Xilinx FPGA. The fundamental characteristics of the implemented beamformer have been measured and verified. The experimental results show that the beamformer is capable of creating appropriate weights in order to steer the main lobe of the ULA antennas to the desired direction and to place simultaneously null points towards the interferences in case of NOAA LEO satellites system.